2019
DOI: 10.1001/jamapediatrics.2019.2825
|View full text |Cite
|
Sign up to set email alerts
|

Association of Use of the Neonatal Early-Onset Sepsis Calculator With Reduction in Antibiotic Therapy and Safety

Abstract: The neonatal early-onset sepsis (EOS) calculator is a clinical risk stratification tool increasingly used to guide the use of empirical antibiotics for newborns. Evidence on the effectiveness and safety of the EOS calculator is essential to inform clinicians considering implementation.OBJECTIVE To assess the association between management of neonatal EOS guided by the neonatal EOS calculator (compared with conventional management strategies) and reduction in antibiotic therapy for newborns.DATA SOURCES Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 146 publications
(173 citation statements)
references
References 64 publications
8
159
5
1
Order By: Relevance
“…Markers of systemic inflammation and immune responses include serial white cell counts and immatureto-mature granulocyte (IT) ratio. [14][15][16][17] Serial full blood count values and IT ratios can predict the absence of early onset sepsis (EOS) with an AUC~0.8 and negative predictive value for proven and suspected sepsis of 99% and 78%, respectively. 12 In addition, CRP and Procalcitonin demonstrate that biomarkers can be useful to shorten antibiotic treatment in patients who improve rapidly after treatment and have negative blood cultures.…”
Section: Current Markers Of Neonatal Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Markers of systemic inflammation and immune responses include serial white cell counts and immatureto-mature granulocyte (IT) ratio. [14][15][16][17] Serial full blood count values and IT ratios can predict the absence of early onset sepsis (EOS) with an AUC~0.8 and negative predictive value for proven and suspected sepsis of 99% and 78%, respectively. 12 In addition, CRP and Procalcitonin demonstrate that biomarkers can be useful to shorten antibiotic treatment in patients who improve rapidly after treatment and have negative blood cultures.…”
Section: Current Markers Of Neonatal Sepsismentioning
confidence: 99%
“…[17][18][19] In addition, a recent meta-analysis and systematic review demonstrated that use of the neonatal EOS calculator is associated with a substantial reduction in the use of empirical antibiotics for suspected EOS. 16 In view of the insensitivity of blood cultures alone to define neonatal infection, other techniques hold promise such as 16s rRNA and PCR which detects <3 copies bacterium. Positives identified by PCR were higher than by blood culture (10 versus 5%) and when blood culture was used as control, the sensitivity and specificity of PCR was 100% and 97.85%, respectively and the index of accurate diagnosis was 0.979.…”
Section: Current Markers Of Neonatal Sepsismentioning
confidence: 99%
“…This may be explained by several factors. First, Gong et al used a fictitious relative reduction of 67% in empiric antibiotic treatment by implementation of the EOS calculator, which is significantly above real-world evidence in the literature [4]. Second, the predicted cost savings were based on American healthcare costs, which are relatively high compared with European countries [16].…”
Section: Discussionmentioning
confidence: 99%
“…It stratifies newborns into three levels of risk with corresponding recommendations for management: (1) no additional care, (2) obtaining a blood culture and monitor vital signs for at least 24 hours, or (3) start treatment with empiric antibiotic therapy after obtaining a blood culture [1,2]. This approach is associated with a reduction of empiric antibiotic treatment for suspected EOS between 41 and 45% compared with conventional strategies [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal empirical therapy of newborns at risk for or with suspected early‐onset sepsis represents the main contributor to the use of antibiotics in early life 4 . There is growing concern about the effects that unnecessary exposure to antibiotics in the perinatal period may have on the future health of these children 5,6 .…”
mentioning
confidence: 99%